Skin atrophy caused by topical glucocorticoids is less common in patients with atopic dermatitis than in those with psoriasis. Issue 2 (9th August 2021) - Lee, Chung Hyeok; Choe, Sung Jay; Kim, Dong Hye; Kim, Eun Jung; Eom, Minseob; Hong, Seung‐Phil; Choi, Eung Ho
Summary: Although the long‐term use of topical glucocorticoids (TGC) may induce skin atrophy including striae distensae (SD), patients with atopic dermatitis (AD) appear to have lesser degree of skin atrophy than those with psoriasis (PSO). Periostin, encoded by POSTN, is involved in tissue remodelling processes of chronic AD lesions. This study was designed to investigate the difference in the occurrence of skin atrophy in patients with AD or PSO when treated with TGC and to elucidate the association between skin atrophy and periostin. Big data analysis using Korean Health Claims Database was performed to determine the prevalence of SD in AD and PSO patients. Blood and skin eosinophils count and dermal fibrosis between AD and PSO patients were compared, and immunohistochemistry for periostin and mRNA sequencing in the dermis were performed. Animal experiments using AD and PSO murine model were conducted. Big data analysis revealed that patients with AD have significantly lesser degree of SD than patients with PSO. The ratio of the dermal fibrous tissues and eosinophil counts were significantly higher in AD patients. In AD skin, periostin was more widely distributed in the entire dermis and POSTN mRNAs were significantly upregulated. Dermal thickness and fibrosis were significantly higher in AD mice even after TGC treatment. A significant positive correlation was observed between dermal fibrosis and tissue eosinophil counts. Lesser skin atrophy in AD patients even after long‐term TGC application could be resulted from skin fibrosis caused by increased tissue eosinophils and periostin deposition.